Carnian bauxite horizon on the Kopitov grič near Borovnica (Slovenia) – is there a »forgotten« stratigraphic gap in its footwall? - Bogomir Celarc (Geologija, 2008)
Beds underlying the Carnian bauxite on the Kopitov gri~ (Slovenia) are by the author’s opinion not Carnian (Cordevolian), but Ladinian age. The considerable stratigraphical gap is presented between Carnian clastic rocks and underlying limestones and dolomites. Bauxite is result of the weathering during the emersion.